Allelic immunoglobulin VH genes in two mouse strains: possible germline gene recombination. - Cohen, J B (1983)
The nucleotide sequence of two germline immunoglobulin heavy chain variable region (VH) genes of mouse BALB/c origin was determined. These two genes are highly homologous to each other. They both have the unusual codon CCT for proline at position 7, which so far has been found only in a specific set of VH genes, called the NPb family. We show that the two VH genes belong to this set. One of our BALB/c genes, VH124, is more homologous to a C57BL/6 NPb VH gene than to any BALB/c VH gene, and we propose that these two genes are alleles. A comparison of the substitutions between these two genes with published sequences of all other BALB/c and C57BL/6 NPb VH genes reveals evidence for past homologous recombination events between related germline VH genes Homologous recombination may play an important role in the diversification of germline immunoglobulin VH genes.